Genetic Parameters of Performance Traits in Crossbred Cattle - Kumar, Pranesh; Dalal, D. S.; Kumar, Sunil; Kumar , Sandeep; Patil, C. S. (International Journal of Livestock Research, 2019)
The present study was conducted on data pertaining to 264 crossbred cattle from the history-cum-pedigree sheets maintained in the Department of Animal Genetics and Breeding, Lala Lajpat Rai University of Veterinary and Animal Sciences, Hisar, Haryana over 19 years (1996 to 2014). The mixed linear model used for analysis was utilized to estimate the genetic parameters of performance traits. Effect of sire group was non-significant on all performance traits. Period of calving significantly affected age at first calving (AFC) and first service period (FSP) only, while season of calving showed significant effect on First peak yield (FPY) and first dry period (FDP). AFC significantly affected first lactation milk yield (FLMY) and FPY. The overall least squares means were 2331.18±52.16 kg, 314.72±9.88 days, 10.86±0.16 kg, 102.46±4.88 days, 1227.41±18.81 days, 131.80±4.82 days and 415.26±4.87 days, for FLMY, FLL, FPY, FDP, AFC, FSP and FCI, respectively. Heritability estimates for FLMY, FLL, FPY, FDP, AFC, FSP and FCI were 0.17±0.19, 0.28±0.19, 0.26±0.22, 0.38±0.23, 0.16±0.14, 0.02±0.17and 0.12±0.18, respectively. The AFC was found to have low to high positive genetic and phenotypic correlation with all others first lactation performance traits. High genetic and phenotypic correlations of FLMY with FPY (0.73±0.12 and 0.51±0.05, respectively) and FLL (0.86±0.18 and 0.58±0.05, respectively) indicated that selection on the basis of FPY will reduce the generation interval, cost of recording and maintaining low producing animal in the herd and will increase the genetic gain in FLMY because of early selection.